2009
DOI: 10.1016/j.biopsych.2008.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Message Tailoring and Self-Relatedness in Smoking Cessation Programming

Abstract: BACKGROUND Smoking leads to illnesses including addiction, cancer, and cardiovascular and respiratory diseases. Different intervention programs have become available. In the past decade, providing tailored smoking cessation messages has been shown to be more effective in inducing smoking cessation than one-size-fits-all interventions. However, little is known about the brain responses of smokers when they receive tailored smoking cessation messages. METHODS A neuroimaging study using blocked and event-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
82
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 18 publications
13
82
0
Order By: Relevance
“…Our results extend prior research on compromised error awareness/processing 6,18,86 and gray matter abnormalities 43,44,66 in drug addiction, offering the intriguing suggestion that impaired insight may drive such effects. Our results also raise the possibility that a specific CUD subgroup (iCUD) might benefit from therapeutic interventions directed at enhancing the neuropsychological mechanisms underlying insight/self-awareness 1 [e.g., self-relevant (tailored) motivational interventions 87,88 ]. More broadly, our results can inform other neuropsychiatric disorders (e.g., anosognosia, alexithymia, schizophrenia, mania) 89 , similarly characterized by impaired insight and disadvantageous, unwanted, or inappropriate behaviors (e.g., leading to violence, self-harm).…”
Section: Discussionmentioning
confidence: 84%
“…Our results extend prior research on compromised error awareness/processing 6,18,86 and gray matter abnormalities 43,44,66 in drug addiction, offering the intriguing suggestion that impaired insight may drive such effects. Our results also raise the possibility that a specific CUD subgroup (iCUD) might benefit from therapeutic interventions directed at enhancing the neuropsychological mechanisms underlying insight/self-awareness 1 [e.g., self-relevant (tailored) motivational interventions 87,88 ]. More broadly, our results can inform other neuropsychiatric disorders (e.g., anosognosia, alexithymia, schizophrenia, mania) 89 , similarly characterized by impaired insight and disadvantageous, unwanted, or inappropriate behaviors (e.g., leading to violence, self-harm).…”
Section: Discussionmentioning
confidence: 84%
“…Both the precuneus and medial frontal cortex are involved in ‘self-referential’ processing 56. Prior neuroimaging studies showed that increased response to personally relevant smoking cessation messages in these brain areas predicted better outcomes (quitting) during a 4-month follow-up 21 57. Thus, precuneus and medial frontal activation may indicate greater self-referential processing that facilitates remembering of the labels.…”
Section: Discussionmentioning
confidence: 99%
“…Neural responses can be recorded as affirmation and subsequent persuasion occur, without requiring self-report assessments that could interfere with the message recipient's natural thought processes. In support of this idea, our team has used neural predictors to augment understanding of health behavior change in response to interventions in other domains (42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Self-affirmationmentioning
confidence: 99%